Changes in banking regulations and the impact on local banks. - Lock, Hoe Yin. (2008)
This study examines the impact of the liberalisation of the domestic commmercial banking sector in Singapore. Objective is to formulate strategies that the local banks should adopt in light of the increased competition from foreign banks.